Biological activities of meroterpenoids isolated from different sources - Fuloria, Neeraj Kumar; Raheja, Radhika K.; Shah, Kaushal H.; Oza, Manisha J.; Kulkarni, Yogesh A.; Subramaniyan, Vetriselvan; Sekar, Mahendran; Fuloria, Shivkanya (Frontiers in Pharmacology, 2022)
Meroterpenoids are natural products synthesized by unicellular organisms such as bacteria and multicellular organisms such as fungi, plants, and animals, including those of marine origin. Structurally, these compounds exhibit a wide diversity depending upon the origin and the biosynthetic pathway they emerge from. This diversity in structural features imparts a wide spectrum of biological activity to meroterpenoids. Based on the biosynthetic pathway of origin, these compounds are either polyketide-terpenoids or non-polyketide terpenoids. The recent surge of interest in meroterpenoids has led to a systematic screening of these compounds for many biological actions. Different meroterpenoids have been recorded for a broad range of operations, such as anti-cholinesterase, COX-2 inhibitory, anti-leishmanial, anti-diabetic, anti-oxidative, anti-inflammatory, anti-neoplastic, anti-bacterial, antimalarial, anti-viral, anti-obesity, and insecticidal activity. Meroterpenoids also possess inhibitory activity against the expression of nitric oxide, TNF- α, and other inflammatory mediators. These compounds also show renal protective, cardioprotective, and neuroprotective activities. The present review includes literature from 1999 to date and discusses 590 biologically active meroterpenoids, of which 231 are from fungal sources, 212 are from various species of plants, and 147 are from marine sources such as algae and sponges.